Combined Scleral Flap with Donor Scleral Patch Graft for Anterior Tube Placement in Glaucoma Drainage Device Surgery - Jea H. Yu; Chuck Nguyen; Esmeralda Gallemore; Ron P. Gallemore (Case Reports in Ophthalmological Medicine)
Purpose. To report a new technique for anterior placement of tubes for glaucoma drainage devices to reduce the risk of tube erosions. Methods. Retrospective review of select cases of Ahmed Valve surgery combined with the novel method of a limbal-based scleral flap covered by a scleral patch graft to cover the tube at the entrance through the limbus. Intraoperative and postoperative illustrations are shown to highlight the method of tube placement. Results. In this retrospective case series, 3 patients are presented illustrating the technique. Two had neovascular glaucoma and one had primary open-angle glaucoma (POAG). On average, intraocular pressure was reduced from 39±14 mmHg to 15±2 mmHg and the number of glaucoma medications was reduced from 4±1 to 0. Preoperative and most recent visual acuities were hand-motion (HM) and HM, 20/60 and 20/50, and 20/70 and 20/30, respectively. Conclusion. The combination of a limbal-based scleral flap with scleral patch graft to cover the tube with glaucoma drainage devices may be an effective means to reduce erosion and protect against endophthalmitis.